2002
DOI: 10.1037/h0086913
|View full text |Cite
|
Sign up to set email alerts
|

Constructing qualitative knowledge in psychology: Students and faculty negotiate the social context of inquiry.

Abstract: Based on interviews with 13 graduate students and 21 faculty from diverse areas of Canadian departments of psychology, I report researchers' views on qualitative methods in terms of social historical, systemic influences on constructing psychological knowledge. These ideological and structural systems include the historical place of qualitative research in scientific psychology, education in alternative research methods, the socioeconomic reward system for faculty, and the potential for changes in the discipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…Given the traditions of psychological education and training, it should not be surprising that there is also a lack of appropriately trained faculty for teaching and mentoring qualitative researchers within psychology departments. Structural constraints are also present along with a lack of theoretical, conceptual, and epistemological support for methodological pluralism (Eakin and Mykhalovskiy, 2005;Rennie et al, 2000;Walsh-Bowers 2002). The place and positioning of courses in qualitative research within psychology departments is, therefore, informed and constrained by the enduring question of the relevance and rigor of qualitative research within the discipline of psychology.…”
Section: Positioning Qualitative Research In Psychologymentioning
confidence: 96%
See 1 more Smart Citation
“…Given the traditions of psychological education and training, it should not be surprising that there is also a lack of appropriately trained faculty for teaching and mentoring qualitative researchers within psychology departments. Structural constraints are also present along with a lack of theoretical, conceptual, and epistemological support for methodological pluralism (Eakin and Mykhalovskiy, 2005;Rennie et al, 2000;Walsh-Bowers 2002). The place and positioning of courses in qualitative research within psychology departments is, therefore, informed and constrained by the enduring question of the relevance and rigor of qualitative research within the discipline of psychology.…”
Section: Positioning Qualitative Research In Psychologymentioning
confidence: 96%
“…Changes, therefore, within psychological research, publication, and teaching have been slow (Danziger, 1994;Rennie, Watson, and Monteiro, 2000;Walsh-Bowers, 2002). While there have been significant advances in the uptake of qualitative research within psychology, including the development of the journal Qualitative Research in Psychology, there continues to be a substantive gap within the curricula of most departments of psychology both in the United States and Canada (Michell, 2004;Ponterotto, 2005a;Rennie et.…”
Section: Positioning Qualitative Research In Psychologymentioning
confidence: 97%
“…We feel that Walsh-Bowers' (2002) account of the development of qualitative research in psychology in Canada was evocative precisely because he drew on material generated in interviews with graduate students and members of faculty, helping to elucidate important contextual influences. We hope that, in the same way, these extracts will illustrate some of the ups and downs of the research process and that, through the citing of concrete examples, readers will find this article of use to them in their research and supervision.…”
Section: Our Aimsmentioning
confidence: 99%
“…Ponterotto's (2005b) survey of qualitative research training on counselling psychology programmes in North America, reported that qualitative methods courses were largely elective and that although 95% of the responding programmes accepted qualitative methods dissertations, only 10% of students had actually conducted qualitative studies in their research. North American writers have described a number of sources of resistance to qualitative research in psychology generally (Walsh-Bowers, 2002) and in professional psychology in particular (Ponterotto, 2005b).…”
Section: The Rise Of Qualitative Research In Professional Psychology mentioning
confidence: 99%
“…This participant feedback was considered a second source of information and a validity check for the research (Moustakas, 1994;Muller & Thompson, 2003;Robson, 2002;Shaw, 2004;Walsh-Bowers, 2002).…”
Section: Research Collection and Analysismentioning
confidence: 99%